2010
DOI: 10.1007/s00784-010-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Different CAD/CAM-processing routes for zirconia restorations: influence on fitting accuracy

Abstract: The aim of the present in vitro study was to evaluate the influence of different processing routes on the fitting accuracy of four-unit zirconia fixed dental prostheses (FDPs) fabricated by computer-aided design/computer-aided manufacturing (CAD/CAM). Three groups of zirconia frameworks with ten specimens each were fabricated. Frameworks of one group (CerconCAM) were produced by means of a laboratory CAM-only system. The other frameworks were made with different CAD/CAM systems; on the one hand by in-laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 30 publications
3
58
0
15
Order By: Relevance
“…This result agreed with previous studies which showed that the CAD/CAM fabrication method produced restorations with better accuracy of fit than conventional casting 3,[5][6][7][8][9] . The choice of zirconia material in this study, i.e., HIP zirconia ceramic versus presintered zirconia ceramic, had no effect on strain development in the all-ceramic frameworks.…”
Section: Strain Developmentsupporting
confidence: 92%
See 1 more Smart Citation
“…This result agreed with previous studies which showed that the CAD/CAM fabrication method produced restorations with better accuracy of fit than conventional casting 3,[5][6][7][8][9] . The choice of zirconia material in this study, i.e., HIP zirconia ceramic versus presintered zirconia ceramic, had no effect on strain development in the all-ceramic frameworks.…”
Section: Strain Developmentsupporting
confidence: 92%
“…It has been pointed out that superstructures fabricated by conventional methods such as casting failed to achieve a passive fit [2][3][4] . When multi-unit fixed restorations were fabricated using the computer-aided design/computeraided manufacturing (CAD/CAM) technique, greater accuracy was achieved [5][6][7][8][9] . The attractiveness of CAD/ CAM fabrication procedures is further boosted with the use of high-strength ceramic materials such as zirconia ceramic 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the mean marginal gaps (calculated by 20 copings per sample series ×24 measurement points per coping) was performed according to the literature 11,18,26,30) as well as by considering the averaged maximum marginal gap within one system or parameter (calculated only by the maximum values of each coping within one sample series). Data are expressed as means with standard deviations and 95% confi dence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The achieved fi tting accuracy is determined by two main factors: the scanner system used for data collection and the milling systems. Regarding the milling systems, it can be distinguished between industrial fabrication and a milling center by providing the CAD data online 1,26) . To date, no study has been conducted to evaluate the impact of various factors within one production line.…”
Section: Introductionmentioning
confidence: 99%
“…84 This processing technique is expected to have a shorter machining time for a less dense material, but one must keep in mind that the final sintering will promote dimensional changes due to shrinkage, which may lead to prosthetic restoration misfit. 85 Although the CAD-CAM systems described above are already well established in the dental market, they present a major drawback related to the great waste of material upon machining. The waste corresponds to approximately 90% of the prefabricated block for a typical restoration 86 and leftovers from these dental restorations are not reusable.…”
Section: Novel Processing Technologiesmentioning
confidence: 99%